Design and Development of a Group Decision Support System for the Evaluation and Selection of Research Projects - Basheleishvili, I.; Bardavelidze, A. (Engineering, Technology & Applied Science Research, 2021)
The current paper deals with the design and development of a web-based group decision support system for the evaluation and selection of research projects. The paper involves the analysis of the system’s requirements, the definition of its functional structure, the development of an algorithm for the evaluation and ranking of research projects, the development of a related database and of a user interface along with the writing of the business logic of the system.